2008
DOI: 10.1159/000142163
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Human Impacted Third Molars: Diversification of Compartments

Abstract: To gain more insight into the development of human teeth, we characterized different compartments of impacted third molars at two developmental stages by assessing expression levels of a set of genes. We considered genes known to be essential for the development of teeth and ectomesenchyme as well as genes covering characteristic features of stemness. Molars were divided into the operculum, periodontal ligament, developing pulp and, using a new approach, the pad-like tissue beneath the developing pulp. Markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 80 publications
0
5
0
4
Order By: Relevance
“…The starting point for this study were our recent reports that identified dental neural crest-derived progenitor cells (dNC-PCs) as good candidates to regenerate neural crest-derived tissues within the craniofacial region (Degistirici et al, 2008;Schoenebeck et al, 2009). As dNC-PCs could be easily differentiated into osteogenic lineages we speculated whether these cells may be useful to engineer facial and jaw skeleton.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The starting point for this study were our recent reports that identified dental neural crest-derived progenitor cells (dNC-PCs) as good candidates to regenerate neural crest-derived tissues within the craniofacial region (Degistirici et al, 2008;Schoenebeck et al, 2009). As dNC-PCs could be easily differentiated into osteogenic lineages we speculated whether these cells may be useful to engineer facial and jaw skeleton.…”
Section: Discussionmentioning
confidence: 99%
“…Surgically removed impacted third molars of young adults were used to prepare dental neural crest-derived progenitor cells (dNCPCs) (Degistirici et al, 2008;Schoenebeck et al, 2009). Written consent was obtained from all parents of the participating patients.…”
Section: Cell Isolation and Expansion Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Os resultados indicaram o modelo de construct viável para o substituto biológico dentário, demonstrando o surgimento de estruturas organizadas tais como: esmalte, dentina, polpa, periodonto; e ligamento periodontal. Schoenebeck et al (2009) Nicodemo (1967) utilizou uma amostra de pacientes brasileiros oriundos do…”
Section: Lista De Figurasunclassified